Literasi Keuangan Ditinjau dari Gender, Etnis dan Agama Mahasiswa di Indonesia - Romauli Nainggolan; Novalita Fransisca Tungka; Natalia Christina (Jurnal Akuntansi dan Pajak, 2022)
Students spending has changed during this pandemic, so they have to manage their finances well. Good financial management is influenced by student financial literacy. This research has four objectives. First, it describes the level of financial literacy of English Literature students in five cities. Second, examine and analyze differences in student financial literacy levels in terms of gender. Third, examine and analyze differences in the level of student financial literacy in terms of religion. Fourth, examine and analyze differences in students' financial literacy levels in terms of ethnicity. The sample of this study was 258 respondents from five universities majoring in English Language Faculty. Therefore, in this study, the t-test was used on the variables of gender, religion and ethnicity. The results of this study reveal four things. First, the category of student financial literacy at a moderate level. Second, there is no difference in student financial literacy in terms of gender. Third, there is no difference in student financial literacy in terms of religion. Fourth, there are differences in student financial literacy in terms of ethnicity. So what needs to be done in the future is the need to increase financial literacy through formal and informal activities for the five ethnic groups above. Keywords : Literasi keuangan, gender, etnis, agama